Model Pengelolaan LA Mart Dalam Meningkatkan Kesejahteraan Karyawan (Study di Desa Drajat Paciran Lamongan) - Siti Maskhanah; Sutopo Sutopo (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
Consumer Behavior or consumer behavior is an action taken by consumers to achieve and fulfill their needs both to use, consume and spend goods and services. In the people of Drajat Village, Banjarwati Village, and Banjaranyar Hamlet, research will be carried out on the Consumer Behavior of the community in choosing halal cosmetic products. This study aims to find out how consumer behavior is in choosing halal cosmetic products in the people of Drajat Village, Banjarwati Village, and Banjaranyar Hamlet. The approach in this research is quantitative research. The population in this study were the people of Drajat Village, Banjarwati, and Banjaranyar Hamlet with 100 people samples taken by probability sampling technique. The independent variable in this study is Consumer Behavior (X) while the dependent variable is the decision to choose halal products (Y). Data collection techniques in this study were questionnaires and observations. Test the instrument using the validity test and reliability test. Data analysis technique using simple linear regression analysis. Based on the results of the study, the test on cultural factors obtained a significance value of Tcount less than Ttable (0.457>0.192), test results on social factors obtained a significance value of Tcount smaller than Ttable (0.356>0.192), test results on personal factors obtained a significance value of Tcount greater than Ttable (0.591> 0.192), test results on psychological factors obtained a significance value of Tcount smaller than Ttable (0.506> 0.192). From this explanation it can be concluded that the personal factor with the PRB indicator code 2 (has the greatest significance value for Consumer Behavior in choosing halal cosmetic products in Drajat Village, Banjaranyar, and Banjarwati Hamlet, namely (0.591> 0.192), then H0 is rejected and Ha is accepted. Meanwhile, other factors have a smaller significance value than personal factors.